1986
DOI: 10.1021/j100281a040
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of the photochemistry of p-benzoquinone in aqueous solutions. 2. Optical flash photolysis studies

Abstract: The mechanism of the photochemistry of p-benzoquinone (BQ) in aqueous solution has been investigated by using optical flash photolysis. The results agree very well with the mechanism developed from the EPR study in the preceding paper. The second-order rate constant for oxidation of water by triplet BQ at pH 7 is estimated to be ~2 X 10s M'1 s'1, while a value of (6.5 ± 0.3) X 107 M'1 s'1 is found for the secondary formation of the semiquinone radical (BQH") according to BQ + BQ-OH" -BQH" + HO-BQ. The Arrheniu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
75
0
2

Year Published

1987
1987
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(82 citation statements)
references
References 0 publications
4
75
0
2
Order By: Relevance
“…[38] This is in contrast to data which indicate that in this system 1,4-benzosemiquinonetype radicals must be minor contributors to photohydroxylation (< 10 %) compared with a non-radical pathway. [37] Based on spin-trapping experiments, it has been suggested [39,44,45] that the first step is an H-abstraction from water [reaction (4)}, that is, that the reaction is analogous to reaction (1).…”
mentioning
confidence: 69%
See 2 more Smart Citations
“…[38] This is in contrast to data which indicate that in this system 1,4-benzosemiquinonetype radicals must be minor contributors to photohydroxylation (< 10 %) compared with a non-radical pathway. [37] Based on spin-trapping experiments, it has been suggested [39,44,45] that the first step is an H-abstraction from water [reaction (4)}, that is, that the reaction is analogous to reaction (1).…”
mentioning
confidence: 69%
“…Such processes have been observed before with many other systems, and with optically active sulfoxides an isomerization is observed; an exciplex as a very short-lived intermediate has been postulated. [87,88] The free-radical intermediates: The formation of free-radical intermediates has been noticed before and has been attributed to the formation of CQH and CQ(OH)H, [32] or only to CQH, [38] and, depending on pH, to their corresponding radical anions. From a flash photolysis study of a 0.4 mm Q solution at pH 7, it was concluded that F(CQH) = 0.47.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…The concentrations of the stock solutions in our experiments were typically 1×10 -3 mol dm -3 . 1,4-Benzoquinones are photosensitive compounds in solution, 7,8,[31][32][33][34][35][36][37] therefore fresh solutions were prepared for all experiments in brown glass volumetric flask.…”
Section: Methodsmentioning
confidence: 99%
“…Esse provavelmente é o principal motivo para a não detecção, ou detecção de valores extremamente baixos, de p-benzoquinona em estudos já publicados envolvendo hidroxilação de fenol monitorados por cromatografia gasosa. Além disso, a p-benzoquinona, em meio aquoso e sob luz, é capaz de clivar as moléculas de água, formando o radical hidroxila [99], [100], [101] . …”
Section: Figura 37 -Estruturas Do Fenol E Dos Compostos Formados Na Runclassified